1990
DOI: 10.1080/00029157.1990.10402908
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging: Improved Patient Tolerance Utilizing Medical Hypnosis

Abstract: Magnetic Resonance Imaging (MRI) is a medical diagnostic procedure which requires a patient to be placed supine into the cylindrical bore of a powerful magnet for approximately one hour. The patient's arms are usually against the sides of the magnet bore with a 3" to 10" space between the patient's face and the top of the magnet bore. This enclosure induces panic and claustrophobic responses in 1% to 10% of the patients undergoing the MRI procedure. There have been many failed diagnostic studies due to patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 9 publications
0
18
0
2
Order By: Relevance
“…This may be due to elevated anxiety levels in the scanner (Friday & Kubal, 1990) and may also explain the failure of regulation to induce HRL decreases in the fMRI study. In support of this interpretation, subjective ratings of the baseline condition (Noanxiety/No-regulation) showed a trend to be higher in the fMRI experiment ( p = .069, paired t test, onetailed).…”
Section: Discussionmentioning
confidence: 97%
“…This may be due to elevated anxiety levels in the scanner (Friday & Kubal, 1990) and may also explain the failure of regulation to induce HRL decreases in the fMRI study. In support of this interpretation, subjective ratings of the baseline condition (Noanxiety/No-regulation) showed a trend to be higher in the fMRI experiment ( p = .069, paired t test, onetailed).…”
Section: Discussionmentioning
confidence: 97%
“…A number of publications analyzed MRI-associated anxiety of patients showing that claustrophobia is a key concern with incidences of up to 65% (1)(2)(3)(4)(5). Such anxieties can become a major problem in some patients thus making repetition of MRI sequences; pharmacologic sedation (6)(7)(8)(9)(10); or other calming measures including musical entertainment (11), psychological preparation (12), and hypnosis (13) necessary. Furthermore, in a substantial number of patients, poor imaging quality due to movement artifacts (9), premature termination of scanning (1), or complete refusal of the patient to carry out MRI must be expected.…”
mentioning
confidence: 98%
“…Studies on claustrophobia, and the development of treatments, were previously largely behavioural 4 [8,9], but more recently, the focus has turned to the role of cognitions. Rachman and colleagues have demonstrated that the experience of claustrophobic anxiety and its reduction is closely related to beliefs about suffocation and restriction, indicating that cognitions play an important role in claustrophobia.…”
Section: Introductionmentioning
confidence: 99%